Corporate Governance and Sustainability Report in Indonesia: Systematic Literature Review Approach - Rochmawati Daud; Inten Meutia; Shelly F Kartasari; Emylia Yuniarti (Jurusan Akuntansi Fakultas Ekonomi Universitas Negeri Surabaya, 2023)
This study examines the literature on corporate governance with sustainability reports to respond to the subsequent questions: How is the development of corporate governance research integrated with sustainability reports in Indonesia, and what governance mechanisms affect sustainability reporting. This study uses a systematic literature review approach to answer the research problem. Using the keywords: sustainability reporting and sustainability report, 19 articles were found sourced from national accounting, economic and business journals in the SINTA 1 to SINTA 4 categories from 2016 to 2020. The amount of research in the accounting field about governance and sustainability reports is still minimal with mixed results, so sustainability report researchers need to conduct a broader and in-depth study. Further research opportunities can be directed by examining the role of governance in sustainability reports for the public sector. Research priorities can be directed toward Audit committee independence, Effectiveness of the Board of Commissioners, Family and Foreign ownership, and Stakeholder pressure